Media credibility and cognitive authority. The case of seeking orienting information - Reijo Savolainen (Information Research: An International Electronic Journal)
Introduction. This article results from a qualitative case study focusing on the information seeking practices of environmental activists. The main attention was devoted to their perceptions of media credibility and cognitive authority in the context of seeking orienting information about environmental issues in particular. Method. The empirical data were gathered in 2005 by semi-structured interviews with twenty environmental activists in Finland. Analysis. The interview data were examined by means of qualitative content analysis by constantly comparing the articulations of media credibility and cognitive authority. Results. The perceptions of media credibility and cognitive authority tend to be dependent on the topic at hand. No specific cognitive authorities were recognized. Sources providing focused information issued by environmental asssociations were perceived as most credible. Newspapers were perceived as less credible due to their political bias and the general level of news reporting. The significance of one's own critical reflection was emphasized in the judgement of the credibility of information sources of various types. Conclusion. Perceived media credibility and cognitive authority significantly, though often implicitly, orient the selection of information sources. There is a need also to explore their role in the context of seeking problem-specific information, both job-related and non-work.